“If there is a declaration of war, we welcome the war”: undi-18, tiktok election, and normalisation of violence - Siti Zuliha Razali,; Muhamad Luqman Hakim Abdul Hani, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Malaysia's democracy has come under attack due to the radicalisation of young and first-time voters on social media platforms. The widespread usage of TikTok as a primary campaign battleground by the political parties during the 15th General Election (GE-15) marks the anomaly pattern of first-time youth voters. Moreover, having social media influencers courting youth voters as a pawn in the electoral war is considered an accentuation of provocation of hate speech, endangering the prospect of moderate democracy in Malaysia. This commentary studies such anomalies by interviewing youth from varying socio-economic standing and educational backgrounds across Malaysia. Our commentary highlights two crucial areas of unexplored terrain for future research. The first is the immediate need to invest in an emancipatory discourse of civic and political education and unabated expansions of democratic space and rights. Secondly, alarming concerns of electoral terrorism and hate speech via social media unravel the under-research angles or assumed organic political divisions between analogue generations of corrupted warlords versus digital politics of technocratic youth savvy. Inadvertently, our observation of the 15th GE has discerned an increasing political worrisome pattern of widespread manipulative tendency by politicians, including using Industrial Revolution 4.0 (IR 4.0) technology to predict the voting pattern and understand the population sentiment through social media. We also conclude that tactics employed by the cyber troopers of political parties have significantly manipulated and poisoned the neutrality and perspectives of first-time youth voters.